RECENT STATUS OF DEMERSAL FISHERY RESOURCES IN THE VIETNAM SEAWATER - Nhuan, Mai Cong; Nghia, Nguyen Viet; Thanh, Tran Van (Vietnam Journal of Marine Science and Technology, 2015)
The report summarizes data of two recent surveys on the demersal fisheries using bottom trawling nets in Vietnamese seawater during 2012 - 2013 under a framework of the project “Comprehensive Assessment of State and Dynamics of Vietnam Marine Resources”. It was indicated that the demersal fisheries resources varied in different surveyed regions and seasons, the Northeast and Southwest monsoons. The species richness was high with 685 species sampled in the Northeast monsoon and 598 species in the Southwest monsoon. For the whole Vietnam seawater, the average Catch per Unit Effort (CPUE) was 55.41 kg/h, the mean of density was 0.66 tons/km2 and the total biomass was 794,188 tons. Regionally, the biomass in the Gulf of Tonkin was 121,775 tons, in the Central region was 363,526 tons, in the Southeast region was 231,375 tons and in the Southwest region was 77,151 tons.